A novel Lactobacillus bulgaricus isolate can maintain the intestinal health, improve the growth performance and reduce the colonization of E. coli O157:H7 in broilers. Issue 5 (3rd September 2022) - Xiang, L.; Ying, Z.; Xue, M.; Xiaoxian, P.; Xiaorong, L.; Chunyang, L.; Yu, W.; Mingcheng, L.; Binxian, L.
ABSTRACT: 1. This study aimed at the effects of a novel Lactobacillus bulgaricus ( L. bulgaricus ) strain and enterohemorrhagic Escherichia coli ( E. coli ) O157: H7 on intestinal flora and growth performance of broilers, and the protective effect of L. bulgaricus on broilers in challenged experiment by E. coli O157: H7 . 2. In vitro bacteriostatic test showed that the cell-free supernatant (CFS) of L. bulgaricus isolate had an obvious inhibitory effect on E. coli O157: H7 . 3. Eighty 1-day-old male broilers were randomly assigned into four treatment groups with four replicates per treatment. All groups received a basal diet in addition to the specific treatments: NC group, gavage with normal saline; In LBP group, gavage with L. bulgaricus isolate (1 × 10 9 CFU/mL) during the whole process and challenged with E. coli O157: H7 (3 × 10 9 CFU/mL); EC group, gavage with E. coli O157: H7 (3 × 10 9 CFU/mL); LB Group, gavage with L. bulgaricus isolate. At the age of 21 d, broilers were weighed and feed conversion ratio (FCR) was calculated. Caecum and caecal contents, ileum and faeces samples were taken after slaughter. 4. The challenge of E. coli O157: H7 resulted in an increase in TLR-4, NF-κB and IL-8 mRNA in caecal tissue, a decrease in Villus: crypt ratio in ileum, a decrease in the overall diversity of intestinal microflora and a poor FCR. 5. The L. bulgaricus isolate decreased the mRNA expression of TLR-4, NF-κB and IL-8 induced by E. coli O157: H7, reduced the content of E. coli O157: H7 in the caecum of broilers, increased the villus: crypt ratio, increased the abundance of beneficial bacteria and overall diversity of intestinal microflora, and improved FCR. 6. The L. bulgaricus isolate can maintain the intestinal health, improve the growth performance of broilers and reduce the colonisation of E. coli O157:H7 in the caecum.